Grammar Translation Method in English Learning Situation: Is it Effective for Increasing Students’ Vocabulary? - Kurniawati, Kadek Lina; Indrawati, Ni Putu Ayu Candra Nora; Fatmawan, Aditya Ridho (Indo-MathEdu Intellectuals Journal, 2025)
This study investigates the role of the Grammar Translation Method (GTM) in enhancing students’ vocabulary development through a Systematic Literature Review (SLR) of relevant studies published between 2014 and 2023. The data were drawn from peer-reviewed journal articles selected using predetermined inclusion and exclusion criteria. Data collection followed the SLR stages of identification, screening, and eligibility, while the analysis employed thematic synthesis to categorize findings across studies. The reviewed literature indicates that GTM consistently contributes to vocabulary development through translation activities, explicit grammar explanations, and structured vocabulary lists. Several studies also show that GTM becomes more effective when combined with modern learning media, such as crossword puzzle applications, comic-based materials, and digital resources. Although GTM originates from traditional language-teaching practices, the findings demonstrate that it continues to support vocabulary acquisition, reading comprehension, and linguistic accuracy across diverse educational contexts. Overall, this review concludes that GTM remains a valuable method, particularly when innovatively modified or integrated with interactive media to meet the needs of contemporary learners